Architecture: Integration of Art and Engineering - Kapliński, Oleg; Bonenberg, Agata; Bonenberg, Wojciech; Lucchini, Marco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The current Special Issue is a synthetic overview of 21 published articles. The contact point of architecture-art-engineering is multidimensional, and therefore, this synthesis of works takes into account three criteria: (a) research subject indication, (b) research problem identification, and (c) sublimation of the research techniques and instrumentality used. Research problems, scientific values, and utility values have been highlighted. This synthetic tripartite is intended to make it easier for the reader to find an interesting subject and instrumentality. As the topics of the articles overlap, guided by the dominant values of each article, five subject groups have been sublimated. These are: structural aspects and design, digitization, architectural heritage, aesthetics and emotions vs. engineering, and interior architecture. The characteristic values of each subject group are presented. The indicated new design and research tools do not separate but combine the subject industries; they connect the entities of the investment process.